KONSEP DIRI PADA REMAJA BROKEN HOME: TINJAUAN PSIKOLOGIS - Mulyanto, Ayu Kharisma Paramita; Cahyo, Amalia Wanda Deva Nur; Isnani, Choirun Nur; Indrianti, Maya Putri; Bakhria, Rizkyatul; lianawati, ayong (Journal of Education Counseling, 2023)
Self-concept is an image or individual perception that includes physical and psychological aspects such as appearance, potential, community acceptance, social interaction, views as a family member, hopes and ideals. Self-concept reflects the way a person sees and understands himself, including identity, feelings of self, and self-image. This study aims to determine the self-concept of adolescents who come from broken homes. The subjects in this study were 21 year old adolescents. This research is a qualitative research with the type of case study research using observation data collection methods, interviews, and documentation and using inductive analysis. Based on the results of the study it was found that individuals who come from broken home families tend to have a positive self-concept even though they come from broken home families. This can be seen from the self-concept aspect, namely that individuals have a fairly good physical appearance and behave according to their gender. In developing self-potential, individuals are good enough to do what they are interested in. Individuals are also able to face stigma and discrimination by society and within the community are also well received. In addition, the individual is highly valued and fully supported by the people around him so that he does not get worse from the problems he is facing. A positive self-concept leads the individual to have an orientation in the future, namely wanting to live a more appropriate life for the family that will be led in the future so that they don't feel what they are feeling at the moment.